Allosteric inhibition of IgE–FcεRI interactions by simultaneous targeting of IgE F(ab’)2 epitopes - Takao Hirano; Akemi Koyanagi; Hideo Ago; Masaki Yamamoto; Jiro Kitaura; Masataka Kasai; Ko Okumura (Communications Biology, 2024)
Abstract Immunoglobulin E (IgE) plays pivotal roles in allergic diseases through interaction with a high-affinity receptor (FcεRI). We established that Fab fragments of anti-IgE antibodies (HMK-12 Fab) rapidly dissociate preformed IgE-FcεRI complexes in a temperature-dependent manner and inhibit IgE-mediated anaphylactic reactions, even after allergen challenge. X-ray crystallographic studies revealed that HMK-12 Fab interacts with each of two equivalent epitopes on the Cε2 homodimer domain involved in IgE F(ab’)2. Consequently, HMK-12 Fab-mediated targeting of Cε2 reduced the binding affinity of Fc domains and resulted in rapid removal of IgE from the receptor complex. This unexpected finding of allosteric inhibition of IgE-FcεRI interactions by simultaneous targeting of two epitope sites on the Cε2 homodimer domain of IgE F(ab’)2 may have implications for the development of novel therapies for allergic disease.